A comparison between prospective Internet-based and paper diary recordings of headache among adolescents in the general population. (April 2016) - Krogh, Anne-Berit; Larsson, Bo; Salvesen, Øyvind; Linde, Mattias
Aim: The aim of this article was to develop and apply an Internet-based headache diary (i-diary) for adolescents and compare it with a paper-diary (p-diary) regarding adherence, user acceptability and recorded headache activity. Methods: In a cross-sectional school-based study, a representative sample of 488 adolescents aged 12–18 years were randomly allocated by cluster sampling to record for three weeks in i-diaries or p-diaries their headache intensity, disability, and use of acute medication. Results: A significantly ( p  = 0.008) higher proportion of adolescents in the i-diary group used the diary at least once during the 21-day period (86% vs 76% for the p-diary). However, the p-diary group completed a significantly ( p  < 0.001) higher number of diary days (20.8 vs 15.0 days for the i-diary). The response rate for the i-diary-group was largely evenly distributed over the study period; conversely, approximately two-thirds of the adolescents using the p-diary responded on all 21 days, whereas one-fourth did not respond at all. The two diary types were rated as equal in easiness to remember ( p  = 0.25), but the i-diaries were more bothersome to use ( p  = 0.029). Conclusion: Although p-diary users completed a higher proportion of diary days, i-diaries provided more reliable and credible estimates of headache parameters because of better real-time assessment.